Bronchiectasis in HIV disease. - Holmes, A; Trotman-Dickenson, B; Edwards, A; Peto, T; Luzzi, G (1992)
An increased frequency of bacterial pneumonia occurs in HIV-infected individuals: however the development of bronchiectasis is not well recognized. We describe seven patients with HIV infection who developed chronic symptomatic lung disease, six with troublesome recurrent infective exacerbations. Bronchiectasis was demonstrated by computed tomography in five patients, and bronchial wall thickening was shown in a further two patients. The characteristics of the patients are described, and possible aetiological factors are discussed. As measures become available which prolong the later stages of HIV disease, bronchiectasis may become an increasing problem in this patient population. Early recognition and appropriate management may significantly alter morbidity in advanced HIV disease.